Characteristics Associated With Consent and Reasons for Declining in a Randomized Trial in Pregnancy. Issue 4 (October 2020) - Mallett, Gail; Hill, Kim; de Voest, Jessica; Bousleiman, Sabine Z.; Allard, Donna; Harris, Stacy; Salazar, Ashley; Clark, Kelly; Ortiz, Felecia; Bartholomew, Anna; Dalton, Wendy; Craig, Jennifer; et al.
Abstract : OBJECTIVE: To evaluate the maternal characteristics associated with consent to a randomized trial of labor induction in pregnancy. METHODS: This is a secondary analysis of low-risk nulliparous women randomized to induction of labor at 39 weeks or expectant management. During the trial, the Data and Safety Monitoring Committee requested additional fields on the screening log, which already included race and ethnicity: maternal age, type of insurance, and the reason for declining consent if declined. RESULTS: From August 2016 (start of additional data collection) to August 2017, 1, 965 (28%) of the 7, 112 eligible women consented to the trial. Consent was more likely for Black women (41%, adjusted odds ratio [aOR] 1.47, 95% CI 1.24–1.74), and less likely for Asian women (15%, aOR 0.64, 95% CI 0.48–0.84), compared with White women (24%). Women without private insurance were more likely to consent (38%, aOR 1.55, 95% CI 1.34–1.79), compared with those with private insurance (22%). Younger women were also more likely to consent. Among eligible women who declined participation and provided a reason (68%), preference to be expectantly managed (85%) was most common, a response more common in Asian women (aOR 1.75, 95% CI 1.31–2.33) and less common in women without private insurance (aOR 0.60, 95% CI 0.51–0.70). Not wanting to participate in research was more common in Asian women (aOR 2.41, 95% CI 1.44–4.03). Declining consent because family or friends objected was more common in Asian women (aOR 2.51, 95% CI 1.27–4.95) and women without private insurance (aOR 1.68, 95% CI 1.10–2.59). CONCLUSION: Frequency of consent and reasons for declining consent were associated with age, type of insurance, and race and ethnicity. These findings should be considered when developing recruitment strategies that promote diverse participant representation. CLINICAL TRIAL REGISTRATION: ClinialTrials.gov, NCT01990612. Abstract : In a randomized trial in pregnancy, frequency of consent and reasons for declining consent were associated with age, type of insurance, and race and ethnicity.